URBAN MUSLIM EDUCATION AND HARMONY IN DIVERSITY: ISLAMIC EDUCATION AT CHRISTIAN MAJORITY SCHOOL IN MANADO CITY - Mumtazul Fikri; Marzuki Marzuki; Ahmad Faizuddin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2022)
This study aims to determine a pattern of harmonization of urban Muslim education in interfaith relations and forms of harmonization in Christian-majority schools in Manado. This research was qualitative research through a case study method. The research data were collected through in-depth interviews, focus group discussions (FGD), observation, and documentation. This research was conducted at the Manado State Senior High School, with the research subjects are the principal, teachers, and students. The results show that the first pattern of harmonization that occurs in urban Muslim education in the city of Manado is accommodation. Second, harmonization of urban Muslim education in Manado occurs in four forms, namely: (1) the existence of Islamic religious teachers; (2) the availability of Islamic education facilities and infrastructure; (3) the ease in performing praying for Muslim students and teachers; (4) the freedom to wear Muslim clothing for women and to use symbols of the Islamic religion in the school; and (5) the facilitation provided by the school to celebrate Islamic holidays (PHBI).